An Analysis of Figurative Language and Its Translation in Avenged Sevenfold’s Song Lyrics - Lukman, Syarif Lukman; Hilman, Evert Haryanto (Asosiasi dosen IDEBAHASA KEPRI, 2023)
The purpose of this research is to achieve a perfect translation so the translated text effortlessly understood through the reader. The object of this research is selected songs from Avenged Sevenfold’s song lyrics. This research focus on 4 types of figurative language which are idioms, personification, metaphor and hyperbole. This research belongs to the area of analysis of the source text and the translated text, which covers a study on annotated translation using introspective and retrospective methods, since the aim of this research is to get a perfect translation the researcher used translation quality theory from Nababan, Nuraeni & Sumardiono (2012), also this research used translation strategies by Chesterman’s (2016) theory and also the other support theories which only focused on semantic and syntactic strategies to analysed the translation strategies of figurative language in selected song lyrics. The result of this research found that trope change is most common semantic strategy used when analysed the data, while scheme change is the most frequent syntactic strategy used in these song lyrics.